Relativism - Baghramian, Maria; Coliva, Annalisa, 1973- (London : Routledge, 2018)
Relativism, an ancient philosophical doctrine, is once again a topic of heated debate. In this book, Maria Baghramian and Annalisa Coliva present the recent arguments for and against various forms of relativism. The first two chapters introduce the conceptual and historical contours of relativism. These are followed by critical investigations of relativism about truth, conceptual relativism, epistemic relativism, and moral relativism. The concluding chapter asks whether it is possible to make sense of relativism as a philosophical thesis. The book introduces readers to the main types of relativism and the arguments in their favor. It also goes beyond the expository material to engage in more detailed critical responses to the key positions and authors under discussion. Including chapter summaries, suggestions for further reading, and a glossary, Relativism is essential reading for students of philosophy as well as those in related disciplines where relativism is studied, such as anthropology, sociology, and politics.
This study offers a critical analysis of relativism. It begins by presenting a historical account of relativistic doctrines from the beginning of western philosophy and then traces how it has become one of the central features of our daily lives.
OCLC-licensed vendor bibliographic record.
Keywords: PHILOSOPHY / General; Relativity